IMPLEMENTASI KEBIJAKAN KERJASAMA PEMERINTAH DENGAN SWASTA (PUBLIC PRIVATE PARTNERSHIP) DALAM PENGELOLAAN SAMPAH DI TPA JATIBARANG (STUDI KASUS KERJASAMA PEMERINTAH KOTA SEMARANG DENGAN PT. NARPATI) - Dwi Arini Setyawati; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2018)
Partnership of Semarang City Government with PT. Narpati in waste management at Jatibarang dumpsite runs for 25 years counted since 2007 until 2032, but the waste volume at Jatibarang until now does not significantly reduced because the waste that processed by PT. Narpati only 250-350 tons (27%-38%) of the total overall amount of waste that goes to Jatibarang that is around 850-900 tons per day. Reports of the work of government agencies (LKj-IP) Semarang City in 2015 mentioned that this partnership did not reach the target with 0% achievments. The purpose of this research is to analyze the implementation of public private partnership in waste management at Jatibarang dumpsite (case study the partnership of Semarang City Government with PT. Narpati). This research uses qualitative descriptive method. To find out how the implementation of this policy, it uses the theory of 5 accuracy by Riant Nugroho which is policy accuracy, implementation accuracy, target accuracy, environmental accuracy and process accuracy. The results of this research shown that the implementation of this partnership policy has not been right nor the policy process. The relationship between Investment & One-Door Integrated Service Office with PT. Narpati less running smoothly because PT. Narpati did not fulfill its obligations to pay contributions. Recommended treat for these problems should be; the newest policy addendum which regulates delinquent contributions, the government must be more facilitative and responsive to helping PT. Narpati, the Government must encourage PT. Narpati as a private sector that wants to cooperate in this type of business that isn’t great demand and hasn’t a large profit value to continue to partnership in managing waste in the Jatibarang dumpsite because in this partnership the Government is more need help from PT. Narpati.